Linking Macroeconomic Indicators To Carbon Emissions In ASEAN Emerging Economies: Empirical Evidence From Panel Data - Tarsan Tarsan; Lela Rospida; Eka Dewi Anggraini (UNIVED Press, 2025)
This study aims to examine the effect of gross domestic product, urbanization, foreign direct investment, and human development index on carbon dioxide (CO₂) emissions in five emerging ASEAN countries (Indonesia, Malaysia, Thailand, the Philippines, and Vietnam) during 2018–2023. The study uses a descriptive quantitative approach with multiple linear regression analysis. Model selection through Chow, Hausman, and Lagrange multiplier tests shows that the random effect model (REM) is the best. Data are sourced from Our World in Data and ASEAN Statistics. The results show that CO₂ emissions have an inverted U-shaped curve. Furthermore, GDP and FDI have a positive and significant effect on CO₂ emissions, indicating that economic activity and investment still depend on fossil fuels. Urbanization has a negative and significant effect, showing that good urban management can reduce emissions. Meanwhile, HDI has a negative but insignificant effect on CO₂.